Praktik Komunikasi Pada Advokasi Kebijakan Nasional Pendidikan Di Daerah (Studi Kasus Dinas Pendidikan Kota Batam) - M, Anggi Heru; Chatra, Emeraldy; Arif, Ernita (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2024)
Based on information from the Rainbow Dew Foundation, an NGO focusing on child protection in Batam City, eleven children received protection throughout 2022 due to physical and sexual violence from classmates and teachers. The research also found that fifteen-year-old children experienced bullying and intolerance in schools, especially from minority ethnic groups in the school. This study aims to identify, describe, and analyze Communication Practices in the Advocacy of National Education Policy by the Batam City Education Office. This research uses a qualitative method with a case study approach and a constructivist paradigm, using the Source Credibility Theory as a reference. The research findings indicate the commitment and strategic steps of the Batam City Education Office in implementing national education policies. Schools take concrete steps, such as the continuous Project Management Officer (PMO) meetings, active participation in technical guidance (bimtek), and persuasive socialization efforts, encouraging relevant parties to actively implement national education policies. Communication, both verbal and non-verbal, plays a crucial role in supporting education policy advocacy at the school level. Key words: Education Policy Advocacy, Child Protection, School Violence, Communication Practices